Individual mental health and mental health of the community - the importance for recovery - Ajduković, Dean (2008)
Severity of trauma exposure affects the whole life of a victim and can change his or her life. The traumatic event also affects the family members, friends and perhaps colleagues at work. This poses a number of important questions, such as: How does exposure to massive traumatic experiences affect the functioning of groups at different levels – from an individual to family to a community? How are these levels related to each other for recovery? Which family factors are important? What is the role of social context factors? Healing from massive traumatization is an interrelated process between individual, family and community levels. If the socio-political circumstances hinder the feelings of safety, fail to create hope and perspective, the healing is slow or does not progress. Cases of disillusioned former war heroes turned into hopeless and aggressive veterans, and data on increasingly negative psychological consequences of prolonged refugee status illustrate this. In the major international multi-site study (Connect project) this has been clearly shown. Effective community-based interventions that facilitate social integration of the communities, decrease social tensions among groups, and provide treatment for the most traumatized individuals are the vehicle for the people to integrate painful collective experiences, so that they can turn toward the future. Thus, the painful task of recovery is not only faced by a traumatized individual but by the whole community as well. The community social reconstruction is a process that can facilitate individual trauma recovery, as it aims at reinstating the norms of social functioning at the level before their downgrading and through which the social fabric of the community is recovered. However, this process faces a number of barriers related to recovery from trauma, such as fragmentation of social life, deep feelings of distrust, complicated grieving. The model integrating such processes will be presented.